Quantification of the Underlying Mechanisms and Relationships Among Cancer, Metastasis, and Differentiation and Development - Yu, Chong; Liu, Qiong; Chen, Cong; Wang, Jin (Frontiers in Genetics, 2020)
Recurrence and metastasis have been regarded as two of the greatest obstacles for curing cancer. Cancer stem cell (CSC) have been found. They contribute to cancer development with the distinct feature of recurrence and resistance to the popular treatments such as drugs and chemotherapy. In addition, recent discoveries suggest that the epithelial mesenchymal transition (EMT) is an essential process in normal embryogenesis and tissue repair, which is a required step in cancer metastasis. Although there are many indications showing the connections between metastasis and stem cell, researchers often studied them separately or at most bi-laterally, not in an integrated way. In this study, we aim at exploring the global mechanisms and interrelationship among cancer, development and metastasis which are currently poorly understood. To start, we constructed a core gene regulatory network which contain specific genes and microRNAs of CSC, EMT and cancer. We uncovered seven distinct states emerged from the underlying landscape. They are identified as Normal, Premalignant, Cancer, stem cell (SC), cancer stem cell (CSC), Lesion and Hyperlasia state. Given the biological definition of each state, we also discussed the metastasis ability of each state. We show how and which types of cells can be transformed to a cancer state and the connections among cancer, CSC and EMT. The barrier height and flux of the kinetic paths are explored to quantify how and which cells switch stochastically between the states. Our landscape model provides a quantitative way which reveals the global mechanisms of cancer, development and metastasis.